2021
DOI: 10.1111/add.15349
|View full text |Cite
|
Sign up to set email alerts
|

The rewarding recovery study: a randomized controlled trial of incentives for alcohol and drug abstinence with a rural American Indian community

Abstract: Aims To test if contingency management (CM) interventions for alcohol and drug abstinence were associated with increased alcohol and drug abstinence among American Indian adults with alcohol dependence who also use drugs. Design In this 2 × 2 factorial randomized controlled trial, American Indian adults with alcohol dependence who also used drugs were randomized to four conditions: (1) incentives for submission of urine samples only (control condition), (2) CM incentives for alcohol abstinence, (3) CM incentiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…The study’s results are consistent with those of another single-site clinical trial conducted in partnership with a Northern Plains reservation–based community, in which 112 participants received a contingency management intervention that was targeted at both alcohol and drug abstinence . In that study, individuals assigned to 3 different contingency management interventions had a higher likelihood of submitting EtG-confirmed alcohol-abstinent urine samples relative to the control group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The study’s results are consistent with those of another single-site clinical trial conducted in partnership with a Northern Plains reservation–based community, in which 112 participants received a contingency management intervention that was targeted at both alcohol and drug abstinence . In that study, individuals assigned to 3 different contingency management interventions had a higher likelihood of submitting EtG-confirmed alcohol-abstinent urine samples relative to the control group.…”
Section: Discussionmentioning
confidence: 96%
“…Qualitative research suggested that contingency management should be adapted to include incentives that supported family relationships and integrated indigenous language and culture . In an initial study of a contingency management intervention that targeted alcohol and drug abstinence in a single Northern Plains community, contingency management was associated with reductions in alcohol and stimulant drug use …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the evidence of the impact of community-based addiction recovery resources, such as mutual support groups with Indigenous people, are scarce [40,41]. Continuous efforts are being made in clinical trials in the United States to improve study design and increase participation rates in research with Indigenous peoples [42].…”
Section: Discussionmentioning
confidence: 99%
“…These adaptations generally were aligned with the ceremonies, practices, and teachings of local communities. In addition, during a contingency management RCT with an American Indian Tribe (resulting in reduced alcohol use within the experimental group), adaptations were made to provide incentives that were culturally relevant to participants, such as providing reinforcers using the community’s Indigenous language as well as gifts such as beading supplies and fishing gear (McDonell et al, 2021).…”
Section: Psychotherapy With Indigenous Clients: Four Pathsmentioning
confidence: 99%